Magnetic carbonyl iron suspension with Ni-Zn ferrite additive and its magnetorheological properties - Hajalilou, A. (Elsevier B.V., 2016)
Ni-Zn ferrite nanoparticles were synthesized via a thermo-mechanical alloying route and adopted as an additive for micron-sized CI-based magnetorheological (MR) fluid. Structure, morphology and magnetic property of the nanoparticles were evaluated through X-ray diffraction pattern (XRD), vibration sample magnetometer (VSM) and transmission electron microscopy (TEM), respectively. The MR characteristics of two fluid systems with and without a nano-sized ferrite additive were studied and compared under different magnetic field strengths using a rotational rheometer. The MR fluid with Ni-Zn ferrite nanoparticles added exhibited remarkably higher yield behaviors, suggesting that the nano-sized ferrite and micron-sized CI particles were being oriented in magnetic field direction under applied field and with strengthened chain-like structure.